Investigation of arbuscular mycorrhizal status and functionality by electrical impedance and capacitance measurement - Takács, Tünde; Füzy, Anna; Rajkai, Kálmán; Cseresnyés, Imre (Acta Biologica Szegediensis, 2014)
Applicability of electrical impedance (EI) and electrical capacitance (EC) measurement for the investigation of root colonization of mixed arbuscular mycorrhizal fungi (AMF) and functional diversity of separated AMF strains were studied in two pot experiments. In the first experiment, mycorrhizal and non-mycorrhizal maize cultivars were compared for testing the sensitivity of EI and EC measurement in relation to mycorrhizal status of host plants. In the second one, root colonization, biomass production, EI and EC of Rhizophagus intraradices or Funneliformis mosseae, inoculated and non-inoculated cucumber and bean hosts were monitored. The mycorrhizal plants showed lower EI and higher EC than control plants for each species. Since fungal colonization did not produce an increase in root surface area of maize, the higher root-soil interface showed by EI and EC values was undeniably due to the increased absorption surface area caused by the growth of AMF hyphae. As for cucumber and bean, the two selected AMF strains differed significantly in infectivity and effectivity, and the measured values also vary with host plants. Measuring EI and EC proved to be well applicable for in situ investigation of functional aspects of mycorrhizae.